The Development of Strategic Management - Strenitzerova, Mariana (Communications - Scientific letters of the University of Zilina, 2005)
The top managers agree on the fact that the development of new strategies is their most important task. However, up to what extent do the time and means expended on the more or less formalized strategic processes really lead to a better efficiency and productivity of the firm? It was dominant task of the study of the German counselling firm The Galileo Consulting Group in cooperation with the European Business School in Oestrich-Winkel. Interactive strategic modelling is a method of an individualizing instrumentarium by means of which it is possible to depict interactively various variant of future actions.